WSCUC Substantive Change Screening Form: Bachelor of Arts in Music
The B. A. in Music is an exciting program that specializes in individualized attention from exceptional faculty who challenge the students to achieve their best. We offer extensive training in musicianship, private lessons, recital repertory classes, and diverse ensembles for students to gain important performance experience. Our dedicated faculty mentor each of our students and this unique individualized special training is the hallmark of our program.Our diverse curriculum design offers students the necessary skills to be at the forefront of the music industry in the twenty- first century. Emphasis will be placed on professional-level performance, current trends in the music industry, pathways to graduate school and music education skills. Special attention will be paid to CSUCI's important role in the diverse Southern California region as a Hispanic Serving Institution. Students will gain a keen awareness of diversity, inclusion, and equity and graduate with multicultural and international perspectives.The B. A. in Music will equip students for a career in a wide array of music-related opportunities including: professional musician, studio recording industry, music educator, music business and marketing positions, composer/arranger/songwriter, and a host of other possibilities.